KEPENTINGAN INDONESIA DALAM DEFENCE COOPERATION AGREEMENT (DCA) DENGAN SINGAPURA PADA TAHUN 2023 - Aini, Nur; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The Defence Cooperation Agreement (DCA) is a formal and binding agreement that regulates defense cooperation between Indonesia and Singapore, including military exercises, territorial access, and defense modernization mechanisms within the framework of international law. As well as focusing on the strategic factors that prompted Indonesia to finally ratify the DCA after being delayed since 2007. This study aims to explain the reasons for the ratification of the DCA using the concept of national interest and the theory of neorealism. This research covers all aspects of Indonesia-Singapore bilateral relations, with a focus on the fields of defense, security, politics and economics. The analysis was carried out by a qualitative method with a descriptive-analytical approach with data sources collected through literature studies and analysis of official documents. The results of the research include aspects, namely first, the security aspect which functions to strengthen the national defense posture, to enhance the professionalism of the Indonesian National Armed Forces (TNI) and expand training capacity through joint exercise mechanisms. Second, political and sovereignty aspects through the resolution of the Flight Information Region (FIR) issue and extradition. Third, economic aspects through the takeover of FIR management and the efficiency of national resource management. Keywords: DCA, Neorealism, national interest, FIR, Indonesia-Singapore relations